Remarkable effect of alkynyl substituents on the fluorescence properties of a BN-phenanthrene - Abengózar, Alberto; Sucunza, David; García-García, Patricia; Vaquero, Juan J. (Beilstein Journal of Organic Chemistry, 2019)
A series of BN-phenanthrenes with substituents of a diverse nature have been synthesized by palladium-catalyzed cross-coupling reactions of a common chloro-substituted precursor, which was made from readily available materials in only four steps. Evaluation of the photophysical properties of the prepared compounds unveiled an impressive effect of the presence of alkynyl substituents on the fluorescence quantum yield, which improved from 0.01 in the parent compound to up to 0.65 in derivatives containing a triple bond.
Keywords: alkyne; BN-phenanthrene; cross-coupling; fluorescence; heterocycles

(untitled) - Wang, X.-Y.; Wang, J.-Y.; Pei, J. (Chem. – Eur. J., 2015)

(untitled) - Campbell, P. G.; Marwitz, A. J. V.; Liu, S.-Y. (Angew. Chem., 2012)
Campbell, P. G.; Marwitz, A. J. V.; Liu, S.-Y. Angew. Chem., Int. Ed. 2012, 51, 6074–6092. doi:10.1002/anie.201200063

(untitled) - Bosdet, M. J. D.; Piers, W. E. (Can. J. Chem., 2009)

(untitled) - Giustra, Z. X.; Liu, S.-Y. (J. Am. Chem. Soc., 2018)

(untitled) - Bélanger-Chabot, G.; Braunschweig, H.; Roy, D. K. (Eur. J. Inorg. Chem., 2017)

(untitled) - Wang, J.-Y.; Pei, J. (Chin. Chem. Lett., 2016)

(untitled) - Nakatsuka, S.; Yasuda, N.; Hatakeyama, T. (J. Am. Chem. Soc., 2018)

(untitled) - Zhang, W.; Zhang, F.; Tang, R.; Fu, Y.; Wang, X.; Zhuang, X.; He, G.; Feng, X. (Org. Lett., 2016)

(untitled) - Li, G.; Zhao, Y.; Li, J.; Cao, J.; Zhu, J.; Sun, X. W.; Zhang, Q. (J. Org. Chem., 2015)

(untitled) - Hashimoto, S.; Ikuta, T.; Shiren, K.; Nakatsuka, S.; Ni, J.; Nakamura, M.; Hatakeyama, T. (Chem. Mater., 2014)

(untitled) - Wang, X.; Zhang, F.; Liu, J.; Tang, R.; Fu, Y.; Wu, D.; Xu, Q.; Zhuang, X.; He, G.; Feng, X. (Org. Lett., 2013)

(untitled) - Wang, X.-Y.; Zhuang, F.-D.; Wang, J.-Y.; Pei, J. (Chem. Commun., 2015)

(untitled) - Wang, X.-Y.; Zhuang, F.-D.; Wang, R.-B.; Wang, X.-C.; Cao, X.-Y.; Wang, J.-Y.; Pei, J. (J. Am. Chem. Soc., 2014)

(untitled) - Wang, X.-Y.; Zhuang, F.-D.; Zhou, X.; Yang, D.-C.; Wang, J.-Y.; Pei, J. (J. Mater. Chem. C, 2014)

(untitled) - Wang, X.-Y.; Lin, H.-R.; Lei, T.; Yang, D.-C.; Zhuang, F.-D.; Wang, J.-Y.; Yuan, S.-C.; Pei, J. (Angew. Chem., 2013)
Wang, X.-Y.; Lin, H.-R.; Lei, T.; Yang, D.-C.; Zhuang, F.-D.; Wang, J.-Y.; Yuan, S.-C.; Pei, J. Angew. Chem., Int. Ed. 2013, 52, 3117–3120. doi:10.1002/anie.201209706

(untitled) - Zhang, W.; Fu, Y.; Qiang, P.; Hunger, J.; Bi, S.; Zhang, W.; Zhang, F. (Org. Biomol. Chem., 2017)

(untitled) - Huang, H.; Pan, Z.; Cui, C. (Chem. Commun., 2016)

(untitled) - Wang, X.-Y.; Yang, D.-C.; Zhuang, F.-D.; Liu, J.-J.; Wang, J.-Y.; Pei, J. (Chem. – Eur. J., 2015)

(untitled) - Liu, X.; Wu, P.; Li, J.; Cui, C. (J. Org. Chem., 2015)

(untitled) - Sun, F.; Lv, L.; Huang, M.; Zhou, Z.; Fang, X. (Org. Lett., 2014)

(untitled) - Bosdet, M. J. D.; Piers, W. E.; Sorensen, T. S.; Parvez, M. (Angew. Chem., 2007)
Bosdet, M. J. D.; Piers, W. E.; Sorensen, T. S.; Parvez, M. Angew. Chem., Int. Ed. 2007, 46, 4940–4943. doi:10.1002/anie.200700591

(untitled) - Morgan, M. M.; Piers, W. E. (Dalton Trans., 2016)

(untitled) - Abengózar, A.; García-García, P.; Sucunza, D.; Frutos, L. M.; Castaño, O.; Sampedro, D.; Pérez-Redondo, A.; Vaquero, J. J. (Org. Lett., 2017)

(untitled) - Abengózar, A.; Fernández-González, M. A.; Sucunza, D.; Frutos, L. M.; Salgado, A.; García-García, P.; Vaquero, J. J. (Org. Lett., 2018)

(untitled) - Bosdet, M. J. D.; Jaska, C. A.; Piers, W. E.; Sorensen, T. S.; Parvez, M. (Org. Lett., 2007)

(untitled) - Lu, J.-S.; Ko, S.-B.; Walters, N. R.; Kang, Y.; Sauriol, F.; Wang, S. (Angew. Chem., 2013)
Lu, J.-S.; Ko, S.-B.; Walters, N. R.; Kang, Y.; Sauriol, F.; Wang, S. Angew. Chem., Int. Ed. 2013, 52, 4544–4548. doi:10.1002/anie.201300873

(untitled) - Hakoda, Y.; Aoyagi, M.; Irisawa, K.-i.; Kato, S.-i.; Nakamura, Y.; Yamaji, M. (Photochem. Photobiol. Sci., 2016)

(untitled) - Yamaji, M.; Maeda, H.; Nanai, Y.; Mizuno, K. (Chem. Phys. Lett., 2012)

(untitled) - Maeda, H.; Maeda, T.; Mizuno, K.; Fujimoto, K.; Shimizu, H.; Inouye, M. (Chem. – Eur. J., 2006)

(untitled) - Abengózar, A.; García-García, P.; Sucunza, D.; Pérez-Redondo, A.; Vaquero, J. J. (Chem. Commun., 2018)

(untitled) - Abengózar, A.; García-García, P.; Sucunza, D.; Sampedro, D.; Pérez-Redondo, A.; Vaquero, J. J. (Org. Lett., 2019)